2017
DOI: 10.1002/dvg.23015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional dynamics of tail regeneration in Xenopus tropicalis

Abstract: In contrast to humans, many amphibians are able to rapidly and completely regenerate complex tissues, including entire appendages. Following tail amputation, Xenopus tropicalis tadpoles quickly regenerate muscle, spinal cord, cartilage, vasculature and skin, all properly patterned in three dimensions. To better understand the molecular basis of this regenerative competence, we performed a transcriptional analysis of the first 72 h of tail regeneration using RNA-Seq. Our analysis refines the windows during whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Studies of the refractory period have also implicated the importance of inflammatory processes during tail regeneration. In regeneration-competent X. tropicalis tadpoles, inflammatory cells are recruited to the wound site over the first 6 h post-amputation (hpa) (Love et al, 2011a), in line with genome-wide studies in Xenopus, which demonstrated an enrichment of inflammation-associated genes during the early phase of regeneration (Aztekin et al, 2019;Chang et al, 2017;Love et al, 2011a). In the refractory period, however, inappropriate activation of the immune system may impair tail regeneration, as immunosuppression improves regeneration in these animals (Fukazawa et al, 2009).…”
Section: Insights Gained From Studying Regeneration In Xenopus Appendmentioning
confidence: 65%
“…Studies of the refractory period have also implicated the importance of inflammatory processes during tail regeneration. In regeneration-competent X. tropicalis tadpoles, inflammatory cells are recruited to the wound site over the first 6 h post-amputation (hpa) (Love et al, 2011a), in line with genome-wide studies in Xenopus, which demonstrated an enrichment of inflammation-associated genes during the early phase of regeneration (Aztekin et al, 2019;Chang et al, 2017;Love et al, 2011a). In the refractory period, however, inappropriate activation of the immune system may impair tail regeneration, as immunosuppression improves regeneration in these animals (Fukazawa et al, 2009).…”
Section: Insights Gained From Studying Regeneration In Xenopus Appendmentioning
confidence: 65%
“…5a), we found that 115 genes (and 37 unique) were responsive to brain removal per se. To characterize the transcriptional response specifically due to brain removal, and not to the removal of any organ in general, we compared the dataset of DEGs after brain removal from our study with the DEGs obtained after tail removal that were identified in two prior studies, in Xenopus 53 and lizard. 54 The tail is large appendage including a massive CNS component (spinal cord) and triggers a robust regenerative response, allowing us to identify and exclude Fig.…”
Section: Brain Is Required For Migratory Response Of Macrophagesmentioning
confidence: 99%
“…All the statistical tests were done using Prism 8. and day 3 (SC_d0d3). The whole tail dataset was obtained from [9]. (E) Tadpoles at NF50 were amputated, fixed at the indicated time and then processed for WISH using a probe specific for foxm1.…”
Section: Statisticsmentioning
confidence: 99%
“…Using Ingenuity Pathway Analysis (IPA), we identified potential upstream regulators that could explain changes in expression of downstream target genes, with Foxm1 showing the highest significance at 3dpa ( Figure 1C). Using published RNAseq of tail regeneration in X.tropicalis [9], we compared changes in expression of known Foxm1 target genes between 0 and 3dpa in whole tail (WT_d0d3), 0 and 1dpa (SC_d0d1) and 0 and 3dpa (SC_d0d3) in spinal cord. Foxm1 and its transcriptional targets are significantly upregulated only in the spinal cord at 3dpa, but not in the whole tail ( Figure 1D).…”
mentioning
confidence: 99%